Aplikasi Web Interaktif Video Animasi Belajar Matematika Usia Dini dengan Soal, Bercerita dan Opini User - Hayati, Ariadi Retno Tri (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
In this application performance for children with interactive education application to learn math. In this application children can learn knowledge about number, operation addition and subtraction in math, two dimensional shape and the last problem is to solve math story questions. In this application provide animation video which use application from RenderForest, and for web application use PHP programing language, Hypertext Preprocessor which use Cascading Style Sheets, Java Script for interactive animation in web. Before use application user can login in application and register first. Each category has some questions and each question has animation video and animation web. Database for this application use Mysql and Xampp application for web application, and for video use renderforest animation application, animation web use CSS and Java Script. Characteristic for question is choice question with one answer for category such as numeric, operasional, and learn shape two dimention, and story solving. For category story use story animation and user can answer one question from a story. Children can give their opinion for each question with click the button in each question. The purpose for this application is make application web and user can give their opinion and there are some animations basic on video and web.